Gis-based scheduling and monitoring of irrigation delivery for rice irrigation system. Part I. Scheduling - Rowshon, M.K; Kwok, C.Y; Lee, T.S (Elsevier, 2003)
A program using geographical information system (GIS) has been developed for the spatial and temporal distribution of irrigation supply for a large-scale rice irrigation project in Malaysia. This study focused on determining water deliveries on a periodic basis during the main (wet) and off (dry) seasons based on spatial and temporal demand. A water balance equation is used to determine the release for each constant head orifice (CHO) within the blocks and compartments. A user interface allows for the selection of a specific area and input of relevant information. The recommended discharges are displayed allowing the manager to view maps, tables and graphs providing a basis for decision making as the season progresses. Comparison of the observed and computed values for the 1997/1998 season in compartment F showed that observed values were higher than the computed values indicating excess supply during the main season. Observed values were lower than computed values during the off-season. The periodic results obtained can then be used to monitor the allocation of irrigation deliveries for improving the water management system. © 2003 Published by Elsevier Science B.V.